Urban Network Economics and the Environment: Insights and Perspectives - Sergio Currarini; Carmen Marchiori; Alessandro Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2014)
Recent research in the field of network economics has shown how explicitly modelling the network structure of social and economic relations can provide significant theoretical insights, as well as account for previously unexplained empirical evidence. Despite their critical importance to many environmental problems, network structures and dynamics have been largely disregarded by the environmental economics literature. This paper aims to begin to fill this gap by analyzing how networks can provide new insights for both theory and practice, and identifying several avenues for future research. The paper addresses questions pertaining to a wide range of issues, including the adoption and diffusion of green technologies, access to and distribution of natural resources, common-pool resource management and governance, and the stability of international environmental coalitions.
Keywords: L14; Q5; O3; 330; Networks; Environmental Externalities; Technological Diffusion; Gas Pipelines Common-pool Resources; Multi-level Governance; Coalitions